PURCHASE DECISION FOR MAYBELLINE LIPSTICK PRODUCTS ON THE TIKTOK SHOP APPLICATION - Pamuji Hari Santoso; Dewi Krisna Samita; Arie Yusnelly (Procuratio : Jurnal Ilmiah Manajemen, 2025)
This research aims to determine the influence of electronic word of mouth, social media influencers, and consumer trust on purchasing decision of Maybelline lipstick on TikTok Shop application in Pekanbaru City. The population in this study was the people of Pekanbaru City, female who had bought Maybelline lipstick at the TikTok Shop. The sampling technique in this research used non-probability sampling with a sample size of 120 respondents. Data was obtained by distributing questionnaires using Google Form. The sampling technique for this research is purposive sampling. The data analysis technique in this research is multiple linear regression analysis technique using the SPSS program. From the results of this research, social media influencers and consumer trust had a significant influence on purchasing decisions for Maybelline lipstick on the TikTok Shop application in Pekanbaru City. Penelitian ini bertujuan untuk mengetahui pengaruh electronic word of mouth, influencer media social, dan kepercayaan konsumen terhadap keputusan pembelian lipstik Maybelline pada aplikasi TikTok Shop di Kota Pekanbaru. Populasi dalam penelitian ini adalah masyarakat Kota Pekanbaru, khususnya perempuan yang pernah membeli lipstik Maybelline di TikTok Shop. Teknik pengambilan sampel dalam penelitian ini menggunakan non-probability sampling dengan jumlah sampel sebanyak 120 responden. Data diperoleh dengan menyebarkan kuesioner melalui Google Form. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling. Teknik analisis data dalam penelitian ini menggunakan analisis regresi linear berganda dengan bantuan program SPSS. Dari hasil penelitian ini, influencer media sosial dan kepercayaan konsumen memiliki pengaruh yang signifikan terhadap keputusan pembelian lipstik Maybelline pada aplikasi TikTok Shop di Kota Pekanbaru.